Cultural determinants of status: Implications for workplace evaluations and behaviors (2014)
Status is a valued workplace resource that facilitates career success, yet little is known regarding whether and how cultural orientation affects status attainment. We integrate status characteristics theory with the literature on individualism and collectivism and propose a cultural patterning in the determinants of status. Four studies (N= 379) demonstrate that cultural orientation influences the tendency to view high status individuals as competent versus warm (Study 1), uncover cultural differences in both individuals' tendency to engage in competence and warmth behaviors to attain workplace status (Study 2) and evaluators' tendency to ascribe status to individuals who demonstrate competence versus warmth (Study 3), and verify that cultural differences in the effects of competence and warmth on status perceptions, and in turn performance evaluations, generalize to real world interdependent groups (Study 4). Our findings advance theory on the cultural contingencies of status attainment and have implications for managing diversity at work. © 2013 Elsevier Inc.